Strategic Risk Management Practices in Nepalese Road Infrastructure Projects : A Qualitative Interview-Based Study - Shahi, Punam (My University, 2026)
Developing the infrastructure especially road sector is an essential part of economic and social development of developing countries such as Nepal. But, there are many problems associated with the planning phase of the road infrastructure projects in Nepal and many of the projects become delayed and over budget. This is a qualitative study to understand the practices of strategic risk management in the planning phase of road infrastructure projects in Nepal, highlighting the difference between international standards (ISO 31000:2018) and the PMBOK Guide and practical implementation in the context of Nepal where it is based on a resource constrained and topographically challenging, multi level federal governance system. The study is based on the interpretivist paradigm, and semi structured interviews with twelve professionals from the Department of Roads, local governments, consultancies, contractors and academia. Thematic analysis was used to analyse the data, based on Braun and Clarke's six phase model, with the use of NVivo software. Patterns in the lived experiences of the participants in identifying, analysing, evaluating, mitigating risks and experiencing the overall effectiveness were identified with this method. Results show that the road sector, in general, has limited formal, experience based and proactive risk management activities in Nepal. The top 7 risk categories that are highly interdependent and dominate the planning phase include geotechnical/topographical risks, land acquisition/social risks, budgetary/financial risks, environmental/regulatory risks, political/governance risks, coordination/stakeholder risks, and design/data/feasibility risks. The approach of risk identification is largely based on field surveys and expert judgement; analysis and evaluation are largely qualitative with little application of formal tools or quantitative analysis. Mitigation strategies are mostly reactive, and involve a mix of engineering solutions and stakeholder engagement. There are governance and co ordination problems related to institutional fragmentation and political influences that limit effective risk management. In general, the current practices are viewed as marginally effective for handling immediate risks, and insufficient for strategic long term risk management. The study validates the conceptual constructs which connect formal standards, institutional context and professional practice. It highlights the importance of formalising risk management mechanisms, improving data quality and feasibility studies, improving inter agency coordination and developing professional and technological capabilities. The recommendations are aimed at complementing international good practices and the reality on the ground, and hence to help achieve more resilient and efficient road infrastructure development in Nepal.
Keywords: risk management; projects; project management; Strategic Project Management; Master’s Programme in Industrial Engineering and Management